Optimized aperiodic broadband visible absorbers. (27th September 2017) - Granier, Christopher H; Lorenzo, Simón G; You, Chenglong; Veronis, Georgios; Dowling, Jonathan P
Abstract: We design a visible wavelength range broadband absorber based on an optimized aperiodic structure, which is capable of almost doubling the absorptance in the visible range, in comparison to tungsten. Our optimized structure is either a tungsten-air or a tungsten-silicon carbide multilayer stack on top of a tungsten substrate. We achieve almost perfect impedance matching between this structure and air. We find that the high absorptance is not related to resonances with high quality factors and no field enhancement is observed, which is in agreement with the broadband and broad-angle absorptance of our structure.